Analisis Konseptual Kurikulum Cinta: Pendekatan Humanistik dan Implikasinya terhadap Pendidikan Islam - Qamariah, Zaitun; Anwar, Khairil (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This research examines the conceptual integration of a love-based curriculum and humanistic approaches within Islamic education frameworks, analyzing their potential implications for learning management systems in Indonesian religious educational institutions.Method – The study employs a systematic library research methodology, analyzing relevant literature published primarily from 2020 onward. Data collection involved comprehensive examination of official policy documents from the Ministry of Religious Affairs of Indonesia, academic journals, and scholarly publications through databases including Google Scholar, ERIC, JSTOR, and DOAJ. Analysis utilized thematic categorization to identify key conceptual elements. Findings – The research identifies three fundamental dimensions of the love-based curriculum: its philosophical foundations in Islamic rahmatan lil 'alamin concept, its pedagogical emphasis on emotional intelligence development, and its practical implementation challenges. The integration of humanistic values with Islamic educational principles creates a framework that enhances character formation while addressing contemporary educational challenges, including digital disruption and social fragmentation. Research Implications – This study contributes to educational theory by proposing a conceptual framework that bridges Islamic educational principles with contemporary humanistic pedagogy. The findings suggest practical applications for curriculum development in religious educational institutions facing modernization challenges. This research presents the first comprehensive conceptual analysis of the love-based curriculum initiative within the context of Indonesian Islamic education, offering insights that extend beyond religious boundaries toward broader educational reform considerations.